2014
DOI: 10.1016/j.euromechflu.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the laminar separation bubble induced transition on the hydrodynamic performance of a hydrofoil

Abstract: The present study deals with the effect of the laminar separation bubble (LSB) induced transition on the lift, drag and moment coefficients of a hydrofoil. A 2D numerical study, based on the SST γ-Re θ transition model of ANSYS-CFX R , is conducted on a NACA66 hydrofoil. Angles of attack range from −4°to 14°and the chord-based Reynolds number is Re = 7.5 × 10 5. An experimental investigation is carried out in the French naval academy research institute's hydrodynamic tunnel based on the measurements of lift, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
3
16
2
Order By: Relevance
“…Between 6°and 8°, it is observed that the lift coefficient deviates from the theoretical linear curve 2π α. This bump in the curve was also observed in simulations with a transition model [17,12], where it could be associated to the position of transition points on the hydrofoil. The inflexion occurs when the pressure side transition point reaches the trailing edge and the transition is close to the leading edge on the suction side.…”
Section: Forward Flowsupporting
confidence: 65%
See 3 more Smart Citations
“…Between 6°and 8°, it is observed that the lift coefficient deviates from the theoretical linear curve 2π α. This bump in the curve was also observed in simulations with a transition model [17,12], where it could be associated to the position of transition points on the hydrofoil. The inflexion occurs when the pressure side transition point reaches the trailing edge and the transition is close to the leading edge on the suction side.…”
Section: Forward Flowsupporting
confidence: 65%
“…The numerical model was defined according to standard recommendations and to a detailed verification process (mesh and time step convergence particularly) achieved in former works in a similar configuration [17,12,32]. The resulting mesh is illustrated in Fig.…”
Section: Numerical Set Upmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the γ − Re θ transition model [37] coupled with the k-ω SST turbulence model (referred to as SST-TM henceforth) has been used at the lowest tip speed ratio. Taking the laminarturbulent transition into account in RANS calculations improves the accuracy of the lift and drag coefficients predictions in presence of transition effects [38,39] and improves the modeling of the dynamic stall [40]. It has also been shown to improve the results of VAWT calculations at low tip speed ratios [16], where blades experience dynamic stall.…”
Section: Turbulence Models and Numerical Proceduresmentioning
confidence: 98%